AL-GHAZALI PERSPECTIVE ISLAMIC EDUCATION CURRICULUM ANALYSIS OF THE CURRICULUM IN SCHOOLS AND MADRASAS IN INDONESIA - Faizin, Mohammad (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
The curriculum is a part that is always closely attached to the education system, especially in Indonesia. The curriculum changes along with the times in the world, and according to the laws in force in Indonesia, the Islamic Education Curriculum is one of the parts that must be taught to students. Considering that Al-Ghazali is a very legendary figure in Islam because through his thoughts he played many roles in the development of the Islamic Education Curriculum, even his thoughts can still be studied to this day and are still able to be applied by certain groups of people. To prove this statement, research was conducted on Al-Ghazali's thoughts on the concept of Islamic education. So that it can be seen that his thoughts are still linked to the existing curriculum, this can be seen through an analysis of the curriculum in schools and Madrasah in Indonesia.